2016
DOI: 10.1186/s13071-016-1802-0
|View full text |Cite
|
Sign up to set email alerts
|

Arbovirosis and potential transmission blocking vaccines

Abstract: Infectious diseases caused by arboviruses (viruses transmitted by arthropods) are undergoing unprecedented epidemic activity and geographic expansion. With the recent introduction of West Nile virus (1999), chikungunya virus (2013) and Zika virus (2015) to the Americas, stopping or even preventing the expansion of viruses into susceptible populations is an increasing concern. With a few exceptions, available vaccines protecting against arboviral infections are nonexistent and current disease prevention relies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 152 publications
0
30
0
Order By: Relevance
“…Interestingly, a recent study has shown that the mammalian vATPase is a ZIKV host factor ( Savidis et al, 2016 ), indicating conserved components of the cellular machinery involved in sustaining viral replication in both hosts. Virus host factors represent potent transmission-blocking targets through multiple approaches, including transgenic gene deletion, small molecule inhibitors and transmission-blocking vaccines ( Bowman et al, 1988 ; Diamond et al, 2002 ; Kang et al, 2014 ; Liu et al, 2014 ; Dong et al, 2015 ; Sandiford et al, 2015 ; Londono-Renteria et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a recent study has shown that the mammalian vATPase is a ZIKV host factor ( Savidis et al, 2016 ), indicating conserved components of the cellular machinery involved in sustaining viral replication in both hosts. Virus host factors represent potent transmission-blocking targets through multiple approaches, including transgenic gene deletion, small molecule inhibitors and transmission-blocking vaccines ( Bowman et al, 1988 ; Diamond et al, 2002 ; Kang et al, 2014 ; Liu et al, 2014 ; Dong et al, 2015 ; Sandiford et al, 2015 ; Londono-Renteria et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The development of virus resistant mosquitoes will require knowledge on virus restriction factors and infection-responsive promoters to express the antiviral genes. Furthermore, multiple research efforts are addressing the inhibition of mosquito-encoded virus agonists (host factors) through small molecule inhibitors, transmission-blocking vaccines and gene deletion ( Bowman et al, 1988 ; Diamond et al, 2002 ; Kang et al, 2014 ; Liu et al, 2014 ; Dong et al, 2015 ; Londono-Renteria et al, 2016 ). The current lack of protective vaccines and drugs for most arboviruses, and the emergence of mosquito resistance to insecticides, have created an increasing need for additional complementary disease control strategies.…”
Section: Discussionmentioning
confidence: 99%
“…One of the immunogens is the mosquito C-type lectin protein (69)(70)(71). Although several trials were studied, research into TBVs that block infection needs more work in the future (70). The immunogen is a homolog of the mammal protein and therefore may induce autoimmune problems.…”
Section: Fig 6 Anti-mosgctl-7 Serum Inhibits Jev Infection In Vivo Anmentioning
confidence: 99%
“…Mosquito proteins related to virus infection were selected as immunogens and showed a role in blocking dengue virus infection. One of the immunogens is the mosquito C-type lectin protein (69)(70)(71). Although several trials were studied, research into TBVs that block infection needs more work in the future (70).…”
Section: Fig 6 Anti-mosgctl-7 Serum Inhibits Jev Infection In Vivo Anmentioning
confidence: 99%
“…New molecular control strategies aimed at blocking pathogen transmission have been proposed, but a better understanding of pathogen-vector interactions is required. 7 We conducted a search in PubMed, Science Direct, and Google Scholar databases for published studies concerning the interaction of the etiological agents of dengue, malaria, and Chagas disease with their respective insect vectors. We compiled a collection of articles from which we selected studies focused on the pathogen molecules involved in the insect invasion, their consequential immune responses, and the current knowledge of control strategies based in the pathogen transmissionblocking.…”
Section: No 1 Enero-febrero De 2018mentioning
confidence: 99%